The Role of Bandung Police Criminal Investigators in Revealing Criminal Cases of Online Fraud Transaction - Zairusi, Zairusi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aimed to determine the role played by the Criminal Investigation Investigators of the National Police in uncovering cases of criminal acts of fraud through online transactions, especially in the Bandung Police Legal Area. The research method used is descriptive analysis method, namely collecting actual data. The data is compiled, processed and analyzed to get the real picture. The implementation of this research was carried out by observation, interviews, literature study, documentation and researching data on activity reports carried out by the Bandung Police Criminal Investigation Unit. The results of the study show that the handling of cases of criminal acts of fraud through online transactions must be with complaints or reports from someone about the existence of a criminal act of fraud and also those who have been deceived or who have been harmed, only then do investigators know that an action that is suspected of being a criminal act of online fraud has taken place. The supporting and inhibiting factors in uncovering cases of fraud through online transactions, the lack of investigators who have the ability and experience in the field of ITE and limitations ITE tools owned by the Bandung Police. Efforts were made to uncover cases of criminal acts of fraud through online transactions to arrest the perpetrators, make appeals to the public and cooperate with state and private agencies.